A risk ranking strategy for network level bridge management - Sathananthan, S.; Rafiq, Meena Imran; Onoufriou, Toula (My University, 2008)
At present almost all bridge owners and managers, i.e. Network Rail, Highways Agency and local authorities in the UK, carryout bridge inspections at regular intervals to collect information on condition and performance of bridges. Introduction of risk based approaches in the selection of inspection regimes can provide consistent safety levels within the network in a cost effective manner. This paper presents the development of a qualitative risk ranking strategy to characterize a network of bridges into groups with similar risk levels, which can form the basis for developing a risk based inspection regime over the network. There are a multitude of factors that affect risk. These factors are identified and rationally combined to present various attributes of bridges. A qualitative scoring system is then introduced which utilizes the attributes to rank bridges in terms of their relative risk. Sensitivity analysis is performed to quantify the effect of relative weights of the attributes on the risk scores. The methodology is demonstrated through its application on UK's Network Rail bridge stock comprising of about 40,000 bridges. The criteria to classify the severity of the attributes are established for the network. A random sample of bridges is ranked to illustrate the proposed methodology. © 2008 Taylor & Francis Group, London.
Keywords: Inspection; Mooring; Life extension